Social Media Post Content Typology and Its Implication for Digital Marketing Strategy: Evidence from Indonesian Hotels - Hartono, Arif; Roostika, Ratna; Muslichah, Istyakara (Journal of Ecohumanism, 2024)
This study aims to classify content typology posted on Instagram by the Indonesian hotel industry and examine which typology increases hotel consumers’ brand engagement, which is currently unexplored. The method used was multiple regression analysis with an ordinary least squares estimator for 1,036 posts from ten different Indonesian hotels posted on Instagram over six months. Regression analysis was used to identify the relationship between the dependent variables (likes and comments) and the independent variables (post typology, week period, month, and characters). Categories’ posts of advertising, events, and promotions have a statistically significant effect on the number of likes. The promotion received the most substantial number of likes of the three categories of posts. In contrast, in the comments model, only category posts of promotion significantly affect the number of comments. An important practical implication is that academics and social media managers can enhance return indicators for interactions in posts and expand the conversation on the sorts of posts and interactions in social media with the help of the study’s findings. Regarding theoretical contribution, this study enriches existing content typology frameworks by applying them to the hospitality industry, particularly in emerging markets like Indonesia.